2013
DOI: 10.1177/0022042613500052
|View full text |Cite
|
Sign up to set email alerts
|

DUI Offenders’ Beliefs About DUI Statutes and DUI Law Enforcement

Abstract: Development of a profile of those who drink and drive is needed to more effectively deter this behavior. Using data from the 2001 NSDDAB (National Survey of Drinking and Driving Attitudes and Behavior), Bertelli and Richardson found that the existence of DUI (driving under the influence) statutes impacts only those least likely to drink and drive, while concern for the likelihood of arrest and individual agreement with the goals of drinking and driving laws significantly reduces propensity for almost everyone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…However, laws also have an impact on offending by providing social deterrence. Such functions have been noted in the literature on drink driving statutes for drinking under the influence (DUI) offences [ 308 , 309 , 310 , 311 ], which are similar to many animal welfare offences in being summary offences [ 312 ]. Deterrence theory focuses on the ability of laws to deter members of society from committing illegal acts, as they believe that offenders will be caught and punished [ 311 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, laws also have an impact on offending by providing social deterrence. Such functions have been noted in the literature on drink driving statutes for drinking under the influence (DUI) offences [ 308 , 309 , 310 , 311 ], which are similar to many animal welfare offences in being summary offences [ 312 ]. Deterrence theory focuses on the ability of laws to deter members of society from committing illegal acts, as they believe that offenders will be caught and punished [ 311 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deterrence theory focuses on the ability of laws to deter members of society from committing illegal acts, as they believe that offenders will be caught and punished [ 311 ]. However, this type of deterrence works primarily for individuals who are least likely to commit offences: as research on DUI enforcement has indicated, individuals who are “extreme drink drivers” are not deterred by the possibility of punishment [ 308 , 309 , 310 ], as visceral and other factors influence the committing of crimes rather than intellect or rational decision-making [ 309 ]. Hence animal protection laws protect welfare through a two-pronged approach: (1) via deterrence which promotes good treatment of animals (because of knowledge that it is illegal to mistreat them), and (2) via punishment of those who act outside of legal norms [ 308 , 309 , 310 , 313 ].…”
Section: Discussionmentioning
confidence: 99%
“…This belief is more common in areas with high injury crash rate and larger number of driving-related offenses (Beck, Yan, Wang, Krens & Burch, 2009). Drunk driving offenders believe that sobriety checkpoints are less common than the general population believes (Goodfellow & Kilgore, 2014). Drunk driving behavior is negatively associated with friends approval of such behavior and belief in high risk of accident or police stop (Greenberg, Morral & Jain, 2004, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Second, many argue that deterrence-based polices are ineffective at controlling drunk driving (DeMichele & Payne, 2013;Freeman & Watson, 2006;Goodfellow & Kilgore, 2014;Taxman & Piquero, 1998;Yu, 2000). Deterrence theory, which many DUI policies are founded upon, assumes consensus lawmaking in that everyone agrees that drunk driving is wrong (Beccaria, 1764(Beccaria, /2003.…”
mentioning
confidence: 99%